2015
DOI: 10.4236/jis.2015.63020
|View full text |Cite
|
Sign up to set email alerts
|

Palm Vein Authentication Based on the Coset Decomposition Method

Abstract: The palm vein authentication technology is extremely safe, accurate and reliable as it uses the vascular patterns contained within the body to confirm personal identification. The pattern of veins in the palm is complex and unique to each individual. Its non-contact function gives it a healthful advantage over other biometric technologies. This paper presents an algebraic method for personal authentication and identification using internal contactless palm vein images. We use MATLAB image processing toolbox to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Our approach also enables the use of low-cost sensors or even wireless biometric systems. For the used segmentation process and feature vectors extraction strategies the reader is referred to the literature [26] [27]. The LDPC code (with appropriate dimension), together with its standard generated matrix, was taken as the decoding strategy and proved to achieve optimal performance in terms of templates matching.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach also enables the use of low-cost sensors or even wireless biometric systems. For the used segmentation process and feature vectors extraction strategies the reader is referred to the literature [26] [27]. The LDPC code (with appropriate dimension), together with its standard generated matrix, was taken as the decoding strategy and proved to achieve optimal performance in terms of templates matching.…”
Section: Resultsmentioning
confidence: 99%
“…In [26] [27] we showed that the biometric imprint (for security reason) is stored in encrypted binary form instead of plain-text. The biometric authentication device should agree access as long as two (enrolled and identified) biometric feature vectors do not differ by more than a definite amount of bits (the threshold).…”
Section: Biometric Matching Algorithmmentioning
confidence: 99%
“…Palm Vein Authentication (PVA), is a digital security technique that uses an individual vein pattern as personal authentication and identification data [14]. The research work outlined in this paper investigates the possibility of introducing Palm Vein Authentication to enhance e-commerce applications in developing countries focusing on Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Palm Vein Identification uses the unique internal vein pattern of the palm as a transactional authentication method. Its benefits are uniqueness, difficult to forge, secure and reliable [14], [15]. This method will help citizens of Nigeria and other developing countries since vein of the palm cannot be easily damaged due to dryness and by citizens engaging in hard labour using the hands.…”
Section: Introductionmentioning
confidence: 99%
“…These systems identify a person by calibrating the authenticity of specific physiological or behavioral characteristics possessed by that person. The physiological characteristics are the physical human traits in particular hand shape, facial recognition, fingerprints, iris scans, ear shapes, skin reflection, finger vein patter recognition and palm vein images, see for example (Xi et al, 2013), (Sayed, 2015a;2015b). The behavioral characteristics of human beings are the way to sign their names, manner of walk, speech patterns, lips motion and keystroke dynamics (Yang, 2010).…”
Section: Introductionmentioning
confidence: 99%